1996
DOI: 10.1002/(sici)1096-8628(19960409)67:2<172::aid-ajmg7>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatry of 18q‐ syndrome

Abstract: Our understanding of neuropsychiatric abnormalities in patients with deletions of the long arm of chromosome 18 (18q- syndrome) is based mainly on sporadic case reports. We characterized the neuropsychiatric phenotype in 27 patients across a wide age range (2-47 years) with breakpoints ranging from 18q22.3-18q21.2. Adaptive behavior scores (Vineland Composite) were significantly higher in females than in males (62 +/- 5 vs. 43 +/- 3). Intelligence ranged from borderline to severely deficient (IQ, 73- < 40), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The association analysis using FBAT of this haplotype with the phenotype psychosis has a biallelic P-value = 0.0773. [26][27][28][29][30][31] Specifically the region of 18p11 has been shown to be associated with psychotic-related disorders in different populations 10,17,32,33 The present study provides additional evidence that a gene related to psychotic disorders lies in this region, and furthermore presents evidence that variation in a specific gene in this region (TGIF) is associated with psychosis in the CVCR population. We previously found association of a specific allele on marker D18S63, in the 18p11.3 region, 10 with psychosis in the CVCR population.…”
Section: Resultsmentioning
confidence: 53%
“…The association analysis using FBAT of this haplotype with the phenotype psychosis has a biallelic P-value = 0.0773. [26][27][28][29][30][31] Specifically the region of 18p11 has been shown to be associated with psychotic-related disorders in different populations 10,17,32,33 The present study provides additional evidence that a gene related to psychotic disorders lies in this region, and furthermore presents evidence that variation in a specific gene in this region (TGIF) is associated with psychosis in the CVCR population. We previously found association of a specific allele on marker D18S63, in the 18p11.3 region, 10 with psychosis in the CVCR population.…”
Section: Resultsmentioning
confidence: 53%
“…Since the genes are not evenly spaced along the chromosome, a physical distance does not correlate with the number of genes and therefore is not any more informative with regard to the number of genes deleted than rank order of breakpoint. While this procedure is similar to that utilized by Kline et al (1993) and Mahr et al (1996), our study differs from previous studies in that we excluded participants with interstitial deletions and mosaicism that were detected because of the higher resolution of our genetic analysis. In addition, our sample was larger and provided more rank order breakpoints [34 different breakpoint regions as opposed to 6 (Kline et al, 1993) and 16 (Mahr et al, 1996) in the previous studies].…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
“…The understanding of the psychological functioning of children with 18q-is based mainly on case studies, which report cognitive abilities from severely impaired to below average (Schnizel, 1984). Although cognitive deficits found with 18q-have been assumed to be related to chromosomal deletion size (Mahr et al, 1996), no study has directly demonstrated this relationship (Kline et al, 1993;Mahr et al, 1996) for a variety of reasons. Kline et al (1993) studied seven individuals with 18q-and proposed that the size of the deletion may be related to the severity of the neurobehavioral phenotype, including brain abnormalities and cognitive deficit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations